PEMILIHAN KEPALA NEGARA DI INDONESIA - Paisal Paisal (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2018)
In the development of law in Indonesia, especially concerning the development of the application of Islamic law, Islamic law experienced ups and downs following the political direction that existed at that time, especially in the context of the election of head of state in Indonesia. It is interesting to raise the theme of the election of the head of state, given the actual dualism of opinions relating to this matter. Is the election of head of state directly from the people or the election of head of state through people's representatives. What really is the desire and purpose of the holders of power in the Unitary State of the Republic of Indonesia. From this phenomenon, the author is very interested in researching further with the focus: